The phenomenon of changing aztreonam susceptibility in Pseudomonas aeruginosa during formation of colistin resistance in vitro - Bocharova Yu.A.; Kuleshov K.V.; Chebotar I.V.; Mayanskiy N.A. (Клиническая микробиология и антимикробная химиотерапия)
Objective.